Pengaruh Booklet Terhadap Pengetahuan Dan Sikap Kesehatan Reproduksi Pranikah Tentang Pencegahan Resiko Kehamilan Di Puskesmas Danau IndahTahun 2023 - Yayah Ratnaningsih; Resi Galaupa (Jurnal Keperawatan Muhammadiyah, 2023)
One of the causes of high death rates for pregnant women is the low knowledge of women's reproduction, especially regarding coping with increasing the knowledge of prospective brides, one of which is by providing health education using booklets. The purpose of this study was to determine the effect of books on the knowledge and attitudes of the bride and groom's reproductive health related to the risk of pregnancy prevention. Quantitative research uses statistical analysis to process research data. The research design was a pre-experimental design with the type of one group pretest-posttest (initial test, single group final test), which means that there was an experimental class that was given a pre-test, then given treatment with Android-based digital pocket book media, followed by giving a post-test to find out increased knowledge of preventing stunting from the preconception period after treatment. The values of the pre-test and post-test were processed and compared using paired t-test to test the research hypothesis. The results showed an increase in reproductive health knowledge after the intervention between the intervention group and the control group (p=0.000 < 0.05) It can be interpreted that booklets can be used to improve reproductive health knowledge and attitudes of prospective brides in preventing pregnancy risks